2012
DOI: 10.1007/s10865-012-9398-0
|View full text |Cite
|
Sign up to set email alerts
|

Who benefits from psychosocial interventions in oncology? A systematic review of psychological moderators of treatment outcome

Abstract: Medical and demographic characteristics and psychological morbidity of individuals with cancer prior to a psychosocial intervention can influence the efficacy of interventions. However, little is known about the moderating role of patients' psychosocial characteristics on intervention effects. This review sought to identify and synthesize the impacts of psychosocial moderators of the effect of psychosocial interventions on the psychological well-being of cancer patients. A systematic review of the published li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 48 publications
2
44
0
3
Order By: Relevance
“…Systematic reviews of intervention studies in which patients acquired new skills and gained confidence to manage their disease show various effects with regard to outcomes such as stress, self-efficacy, and HRQoL [13, 15, 16, 28]. For instance, findings from a literature review of randomized controlled trials (RCT) by McGregor and Antoni demonstrate reduced levels of stress following cognitive behavioral interventions in women treated for breast cancer [11], similar to results from the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Systematic reviews of intervention studies in which patients acquired new skills and gained confidence to manage their disease show various effects with regard to outcomes such as stress, self-efficacy, and HRQoL [13, 15, 16, 28]. For instance, findings from a literature review of randomized controlled trials (RCT) by McGregor and Antoni demonstrate reduced levels of stress following cognitive behavioral interventions in women treated for breast cancer [11], similar to results from the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Tamagawa et al [28] summarized the benefits from psychosocial interventions in oncology: the types of interventions were as follows: cognitive-behavioral stress management cognitive behavioral therapy; expressive writing, support group alone; psychoeducation, support group plus psychoeducation; psychoeducation and life style and coping training; individual supportive counseling; a booklet including self-management skills and stories of other patients' experiences; and a booklet for treatment decision making. The results indicated that those with low levels of self-efficacy initially benefited from psychosocial interventions, while those with higher levels of self-efficacy at baseline did not [28]. Similar to our findings, educational interventions have led to improvements in HRQoL in other cancer populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The types of psychotherapy approaches in cancer patients with depression are vast (from cognitive-behavior therapy to existential-based intervention, from psychodynamically oriented therapy to educational, relaxation, expressive-supportive therapy, and other forms of treatment, such as mindfulness), supporting the view that it is more important to focus on participants’ variables (e.g., level of depressive symptoms, type and stage of cancer, personality variables) [68] rather than the type of intervention itself [69, 70]. For example, a systematic review [71] examining 199 potential papers, of which a total of 20 studies were selected and involved 3,340 heterogeneous cancer patients, showed that cancer patients who had the greater benefit from intervention were those who reported low levels of optimism and neuroticism; high levels of emotional expressiveness, interpersonal sensitivity, and dispositional hypnotisability; and poorer quality of life, interpersonal relationships, and sense of control.…”
Section: Interventionmentioning
confidence: 99%
“…beliefs about personal abilities to control the illness). Higher personal control has been shown to be related to patients' psychosocial and physical well-being (Ashley, Marti, Jones, Velikova, & Wright, 2015;Hagger & Orbell, 2003;Tamagawa, Garland, Vaska, & Carlson, 2012). Personal control is one of the components of illness perceptions in Leventhal's Common Sense Model (Leventhal, Nerenz, & Steele, 1984).…”
mentioning
confidence: 99%